Aligners: General Characteristics, Advantages, and Disadvantages (Review) - Mehmani , Ilham Gasanaga; Mehmani, Vusala Rasim; Ashrafov, Davud Sergey; Kerimova, Gulyara Elhan (Actual Dentistry, 2025)
Abstract. In the past decade, removable orthodontic thermoplastic appliances—aligners—have become a widespread alternative to traditional fixed systems and orthodontic devices designed to correct malocclusion by applying forces that induce specific tooth movements. The technology used in the production and application of aligners enables the development of a customized alignment system with complete control over desired thickness, coverage, and attachments. The purpose of the review is to examine the methods and options for modeling removable orthodontic appliances—aligners—and to analyze the technologies used to produce them. Results. The main advantages of using aligners are their invisibility during wear, which makes them aesthetically very attractive, and the ease of self-maintenance of oral hygiene. Also, aligners protect the oral mucosa and eliminate the risk of enamel damage, as they contain no hard metal or ceramic components. Instead, they use soft, biocompatible material locks. Ease of adaptation and the absence of a foreign body sensation in the mouth also distinguish aligners from other methods of dental correction. The disadvantages of aligners include their limited functionality, since they cannot be used to treat patients with severe occlusion (for example, in cases of large diastemas or gaps between the teeth), as well as their relatively high cost. Conclusion. The modern method of treating malocclusion with aligners allows for correcting dental disorders and providing comfortable orthodontic treatment for the patient. Aligners have excellent prospects for the future due to their simplicity, practicality, and patient convenience.